MICROBIAL DIVERSITY ASSOCIATED WITH DIFFERENT FRESH MEATS SOLD IN ABA METROPOLIS, ABIA STATE, NIGERIA - C. C., Ike,; E. E., Akortha, (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
The microbial diversity associated with different fresh meat samples: intestine, hide (Kpomo) and beef were analyzed using standard microbiological methods. The microbial loads were high in mean aerobic, coliform and fungi counts (CFU/g) in samples of intestine (3.0 x105) ±0.12, (2.3 x104) ±0.09, (0.9 x104) ±0.14, while the least counts were among samples of beef: (1.2 x103) ±0.16, (0.4 x102) ±0.02, (0.6 x102) ±0.33 respectively. Nine bacterial and nine fungal isolates were identified with their percentage prevalence to include Aeromonas (71%), Pseudomonas (65%), Salmonella (44%), Clostridium (43%), Enterococcus (43%), Alcalegenes (41%), Staphylococcus (38%), Escherichia coli (35%), Bacillus (34%), and fungi: Mucor (65%), Rhizopus (63%),, Candida (59%), Torulopsis (55%), Rhodotorula (40%), Aspergillus (39%), Cryptococcus (37%), Fuarium (33%), and Penicillium species (31%). The presence of these organisms in high thresholds is indicative of serious non-conformity and looming food borne outbreaks, if unchecked. Therefore, there is need for urgent awareness training among stakeholders (butchers/ sellers and teeming consumers) on the inherent risks associated with the crude practices in order to avert the looming food borne outbreaks